Therapeutic Potential of the Rhizomes of Anemarrhena asphodeloides and Timosaponin A-III in an Animal Model of Lipopolysaccharide-Induced Lung Inflammation - Park, Byung Kyu; So, Kyung Su; Ko, Hye Jung; Kim, Hyun Joong; Kwon, Ki Sun; Kwon, Yong Soo; Son, Kun Ho; Kwon, Soon Youl; Kim, Hyun Pyo (Biomolecules & therapeutics, 2018)
Investigations into the development of new therapeutic agents for lung inflammatory disorders have led to the discovery of plant-based alternatives. The rhizomes of have a long history of use against lung inflammatory disorders in traditional herbal medicine. However, the therapeutic potential of this plant material in animal models of lung inflammation has yet to be evaluated. In the present study, we prepared the alcoholic extract and derived the saponin-enriched fraction from the rhizomes of and isolated timosaponin A-III, a major constituent. Lung inflammation was induced by intranasal administration of lipopolysaccharide (LPS) to mice, representing an animal model of acute lung injury (ALI). The alcoholic extract (50-200 mg/kg) inhibited the development of ALI. Especially, the oral administration of the saponin-enriched fraction (10-50 mg/kg) potently inhibited the lung inflammatory index. It reduced the total number of inflammatory cells in the bronchoalveolar lavage fluid (BALF). Histological changes in alveolar wall thickness and the number of infiltrated cells of the lung tissue also indicated that the saponin-enriched fraction strongly inhibited lung inflammation. Most importantly, the oral administration of timosaponin A-III at 25-50 mg/kg significantly inhibited the inflammatory markers observed in LPS-induced ALI mice. All these findings, for the first time, provide evidence supporting the effectiveness of and its major constituent, timosaponin A-III, in alleviating lung inflammation.